HOW TO PLAN A LESSON (A CASE STUDY AT STMIK MARDIRA INDONESIA) - . Marjito (STMIK Mardira Indonesia, Bandung, 2015)
In this paper, I would like to reveal “how to plan a lesson” which is conducted by English lecturer at Sekolah Tinggi Manajemen Informatika dan Komputer (STMIK) Mardira Indonesia Bandung compared with “how to plan a lesson” based on Brown (1994:395). Are there any relevance between them? Keywords: how to plan a lesson, Brown Abstrak Dalam tulisan ini , saya ingin mengungkapkan